ANALISIS IMPLEMENTASI ISAK NO 35 TENTANG PELAPORAN KEUANGAN ENTITAS NIRLABA (STUDI KASUS PADA PARTAI KEBANGKITAN BANGSA KABUPATEN KOTA PADANGSIDIMPUAN) - Lubis, Putri Rezki Rahmadini; Prayogo, Youdhi; Budianto, Achyat (Lembaga Pengembangan Kinerja Dosen, 2023)
Political parties are non-profit organizations and for-profit entities. DSAK IAI ratified the Interpretation of Financial Accounting Standards (ISAK 35). The purpose of this study was to determine the implementation of financial reporting at the National Awakening Party, Padangsidimpuan City Regency, in accordance with what was stated in ISAK No. 35 and to find out the inhibiting factors for the discrepancy between political party accountability financial reports and ISAK No. 35. This research used a qualitative research type. The results of the study show that the Padangsidimpuan DPC PKB only makes an accountability report on the use of funds sourced from the APBD every year in accordance with Permendagri No.78 of 2020. The inhibiting factors are the discrepancy in the presentation of the financial statements of the Padangsidimpuan DPC PKB, namely; lack of knowledge and information regarding the preparation of financial reports in accordance with ISAK No. 35, lack of education about ISAK 35 to financial managers of the DPC PKB Padangsidimpuan City, lack of resources such as non-existent asset procurement and party officials who have no economic or accounting background.